Purifying the Faith : The Muhammadijah Movement in Indonesian Islam - Peacock, James L. (Book collections on Project MUSE., 2019)
The Muhammadijah (or Muhammadiyah) movement was founded by Ahmad Dahlan in 1912 and evolved to emphasize religious and secular education, personal moral responsibility, and a tolerance for other faiths. It is the second largest Islamic organization in Indonesia with an estimated 30 million followers. In 1970, James L. Peacock spent eight months in Indonesia immersing himself in the thinking, religious practice, and daily lives of Muhammadijah followers. Published in 1978, this historical and ethnographic study was one of the first books about this major Islamic reform movement and is considered an insightful and relevant work to this day.